2015
DOI: 10.1177/2373379915616646
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Conducting a Dissertation Study Through the Community-Based Participatory Research Approach

Abstract: The community-based participatory research (CBPR) approach has been shown to be innovative and effective in conducting research with communities experiencing health disparities. Doctoral nursing students, and other doctoral students in the health sciences, who are interested in this approach can benefit through structured CBPR training experiences in learning how to engage with communities, build community capacity, share resources, implement CBPR study plans, and disseminate results of CBPR-focused studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The included studies were mapped onto the KTA cycle [ 29 ] based on the reported research purpose and objectives, as follows: identify problem ( n = 30) [ 37 – 67 ]; adapt knowledge to local context ( n = 34) [ 37 40 , 43 , 44 , 46 , 49 , 52 , 55 , 56 , 61 , 62 , 64 , 65 , 67 – 86 ]; assess barriers/facilitators to knowledge use ( n = 14) [ 39 , 40 , 52 , 56 , 63 , 68 , 72 , 74 , 81 , 83 , 87 – 90 ]; select, tailor, implement interventions ( n = 11) [ 56 , 63 , 68 , 80 , 81 , 83 , 88 – 92 ]; monitor knowledge use ( n = 25) [ 55 , 63 – 65 , 69 , 73 , 80 , 83 , 89 , 91 107 ]; evaluate outcomes ( n = 22) [ 48 , 50 , 51 , 62 , 64 , 68 , 71 , 79 , 83 , 91 , 93 , 95 , 100 – 110 ]; sustain knowledge use ( n = 1) [ 79 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were mapped onto the KTA cycle [ 29 ] based on the reported research purpose and objectives, as follows: identify problem ( n = 30) [ 37 – 67 ]; adapt knowledge to local context ( n = 34) [ 37 40 , 43 , 44 , 46 , 49 , 52 , 55 , 56 , 61 , 62 , 64 , 65 , 67 – 86 ]; assess barriers/facilitators to knowledge use ( n = 14) [ 39 , 40 , 52 , 56 , 63 , 68 , 72 , 74 , 81 , 83 , 87 – 90 ]; select, tailor, implement interventions ( n = 11) [ 56 , 63 , 68 , 80 , 81 , 83 , 88 – 92 ]; monitor knowledge use ( n = 25) [ 55 , 63 – 65 , 69 , 73 , 80 , 83 , 89 , 91 107 ]; evaluate outcomes ( n = 22) [ 48 , 50 , 51 , 62 , 64 , 68 , 71 , 79 , 83 , 91 , 93 , 95 , 100 – 110 ]; sustain knowledge use ( n = 1) [ 79 ...…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 summarizes the key barrier themes identified from the included papers. Trainees’ lack of knowledge and skills posed challenges for IKT research [ 48 , 71 , 72 , 74 , 79 , 84 , 97 , 109 ]. IKT knowledge and skills were related to knowing how to apply an IKT approach and specific procedural techniques related to IKT research processes.…”
Section: Resultsmentioning
confidence: 99%
“…Nadimpalli, Van Devanter, Kayathe, and Islam (2016) share that CBPR work can be conducted with doctoral students. While CBPR is quite involved, they make a case that public health education specialists need not wait until they work several years in the field but can benefit from this experience as graduate students.…”
mentioning
confidence: 99%